CMOS-compatible Eu2+-doped CsCu2I3 films with improved quantum yield for white-light emission and information encryption - Daoping Peng; Lichun Zhang; Xiaoxuan Li; Xiao Zhang; Yu Fang; Chenxi Han; Ziyan Wan; Xiaohua Cheng; Guanying Xie; Zhongqiang Wang; Congcong Liu; Mengmeng Jiao; et al. (Chemical Engineering Journal, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Dendrobium officinale polysaccharide prevents liver injury via the regulation of Keap1/Nrf2 pathway and lipid metabolism in acute alcoholic liver injury mice - Mei Zhou; Niu Zhenpeng; Ruhai Chen; Heng Luo; Jinyu Li; Enming Hu; Ying Yang; Yangming Jiang; Qing Li; Daoping Wang; Weidong Pan (Natural Product Research, 2026)

Regulation of cadmium accumulation and transport in plants by exogenous calcium in acid yellow soils - Shaoxia LIN; Qiuxiao YAN; Fuxiao WEI; Guangyan LIANG; Daoping WANG (Pedosphere, 2026)

Spatiotemporal Patterns of Echolocation Activity of the Yangtze Finless Porpoises ( Neophocaena asiaeorientalis ) Near Mid‐Channel Islands in the Yangtze River - Daoping Yu; Kangwei Wang; Minmin Chen; Yuxi Lian; Longfei Huang (Marine Mammal Science, 2026)
Understanding fine‐scale habitat use is essential for conservation of endangered freshwater cetaceans in large rivers. Although Yangtze finless porpoises ( Neophocaena asiaeorientalis ) are frequently observed near mid‐channel islands, their spatiotemporal use of different island geomorphic units remains poorly resolved. From January 2021 to July 2022, passive acoustic monitoring was used to investigate echolocation activity of porpoises at three geomorphic units (head, middle, and tail) of Qingjiezhou Island in an anabranching reach of the Yangtze River. Porpoise acoustic activity exhibited significant seasonal and spatial variation. During the wet season, both daily detection rate (DDR) and sequent log window (SLW) were highest at the island middle and tail, whereas activity during the dry season was greatest at the island head, likely influenced by fish aggregation associated with sluice gate operation. Spatial heterogeneity in echolocation activity among geomorphic units was significant during the wet season but less pronounced during the dry season. A strong positive correlation was observed between DDR and mean daily SLW, indicating consistent patterns of habitat use intensity. Our findings demonstrate that mid‐channel islands function as seasonal mini‐floodplains and critical habitats for Yangtze finless porpoises, underscoring the importance of incorporating island geomorphic units into conservation planning for large river ecosystems.

Establishment of a TRV-based virus-induced gene silencing system using the vacuum infiltration in Tartary buckwheat - Huala Wu; Xin Li; Shengchun Li; Jianping Hu; Yuanbin Mao; Daoping Zeng; Qilong Qin; Tao Wang; Chenglei Li; Haixia Zhao; Qi Wu (Plant Cell Reports, 2026)

Rosa roxburghii Tratt juice ameliorates fluoride exposure-induced bone metabolism disorders by modulating gut microbiota and serum metabolites - Zhenting Zhang; Sixiu Zhong; Ruihua Zhang; Qibing Zeng; Pinggui Lei; Wenjin Qiu; Wang Chen; Daoping Wang; Xinjing Wei; Qun Huang; Ting Hu; Peng Luo (Food Research International, 2025)

Effect of sterically hindered amines on the cycling capacity of biphasic absorbents for industrial CO2 capture - Zanbu Geng; Le Fu; Yang Yang; Yixi Wang; Wenqing Xu; Runlong Hao; Daoping Zhan; Tingyu Zhu (Journal of Environmental Sciences, 2025)

Efficiently extending the carbon-chain of branched light alcohols derived from bio-ethanol upgrading for sustainable aviation fuels - Kaili Wang; Daoping Lin; Yayun Pang; Chenglei Xiao; Kongqian Liang; Zhaoxi Cai; Jinpeng Liang; Jinliang Song; Tiejun Wang (Chemical Engineering Journal, 2025)

Customized multifunctional interlayer with bismuth‑vanadium dual active sites bidirectionally accelerates the polysulfide conversion for lithium–sulfur batteries - Junhui Si; Haonan Zhang; Sen Zeng; Qianting Wang; Daoping Cai; Zhixiang Cui; Xiaolong Liu (Chemical Engineering Journal, 2025)

Insight into the rutin biosynthesis in the unique flavonol synthesis pathway of Tartary buckwheat based on the enzymatic functions of FLSs - Chenglei Li; Jiayi Sun; Guanlan Shi; Xuerong Zhao; Jun Gu; Jiaqi Shi; Qihan Ma; Daoping Zeng; Tao Wang; Zizhong Tang; Tongliang Bu; Hui Chen; et al. (Theoretical and Applied Genetics, 2025)

Seasonal patterns and environmental drivers of atmospheric microplastics in a coastal megacity - Qilong Jia; Yusen Duan; Zhaofeng Song; Xiaolin Han; Xiaochong Wang; Limin Wang; Daoping Song; Jia Chen; Guangli Xiu (Environmental Research, 2025)

Integrating supply chain social responsibility and environmental commitment for sustainable green supply chain operations - Shafiul Bashar; Daoping Wang; Marwah Rafiq (Journal of Environmental Management, 2025)

Effects of different eco-stoichiometric ratios of calcium and cadmium on the detoxification mechanisms of Capsicum annuum L. under cadmium stress - Qiuxiao Yan; Shaoxia Lin; Fuxiao Wei; Tingfei Deng; Yin Yang; Zhenming Zhang; Daoping Wang (Journal of Hazardous Materials, 2025)

Selective sublimation of Zn to prepare NiZn/SiO2 catalysts for dry reforming of methane: Insight of synergistic catalysis and anti-coking - Saisai Jin; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2025)

Cascading effect modelling of integrating geographic factors in interdependent systems - Yong Ge; Mo Zhang; Rongtian Zhao; Die Zhang; Zhiyi Zhang; Daoping Wang; Qiuming Cheng; Yuxue Cui; Jian Liu (Environmental Modelling & Software, 2025)

Overexpression of AtbZIP69 in transgenic wheat confers tolerance to nitrogen and drought stress - Jiji Yan; Daoping Wang; Zhang He; Xin Li; Wensi Tang; Kai Chen; Yongbin Zhou; Youzhi Ma; Ming Chen (Planta, 2025)

Does the rebound effect offset low-carbon gains from technological progress in China's transportation sector? - Caiquan Bai; Xing Yi; Daoping Wang (Science of The Total Environment, 2024)

Research on heavy metal enrichment and transportation in tea plant-soil systems of different varieties - Shaoxia Lin; Xiaolan Liu; Qiuxiao Yan; Guangyan Liang; Daoping Wang (Environmental Geochemistry and Health, 2024)

Cascade effects of global supply chains induced by regional conflicts increase global inequality - Rongtian Zhao; Daoping Wang; Yong Ge; Mo Zhang; Die Zhang; D'Maris Coffman; Qiuming Cheng (Resources, Conservation and Recycling, 2024)

Water consumption and biodiversity: Responses to global emergency events - Dandan Zhao; Junguo Liu; Laixiang Sun; Klaus Hubacek; Stephan Pfister; Kuishuang Feng; Heran Zheng; Xu Peng; Daoping Wang; Hong Yang; Lei Shen; Fei Lun; et al. (Science Bulletin, 2024)

Designing a size exclusion-based hapten and the development of a quantitative and visual time-resolved fluorescence immunochromatography assay strip for detecting dimethomorph and flumorph in a group-specific manner - Yuxian Zhu; Yongyi Zhang; Daoping Zeng; Haoyu Chen; Yu Wang; Jinyi Yang; Hong Wang; Zhenlin Xu; Yuanming Sun; Yuanxin Tian; Yudong Shen (Food Chemistry, 2024)

The fungi of Dictyophora genus and its by-products: Recent progress towards the development of novel food formulations - Ningxian Yang; Daoping Wang; Xin Li; Hongying Li; Shuang Luo; Kaiju Zhang; Peng Luo (Food Bioscience, 2024)

Dynamic game strategies and coordination of closed-loop supply chain considering product remanufacturing and goodwill in the big data environment - Genhasi Ge; Daoping Wang; Sihan Liang (Environment, Development and Sustainability, 2024)

Applications of advanced materials in the pretreatment and rapid detection of small molecules in foods: A review - Zhizhou Ling; Jinyi Yang; Yongyi Zhang; Daoping Zeng; Yu Wang; Yuanxin Tian; Hong Wang; Zhenlin Xu; Yuanming Sun; Yudong Shen (Trends in Food Science & Technology, 2023)

Leveraging opportunity of low carbon transition by super-emitter cities in China - Heran Zheng; Zengkai Zhang; Erik Dietzenbacher; Ya Zhou; Johannes Többen; Kuishuang Feng; Daniel Moran; Meng Jiang; Yuli Shan; Daoping Wang; Xiaoyu Liu; Li Li; et al. (Science Bulletin, 2023)

CSR’s impact on COVID-19 labor environmental issues: evidence from Bangladeshi SMEs (ISO 26,000) - Shafiul Bashar; Daoping Wang; Marwah Rafiq (Environment, Development and Sustainability, 2023)

Adoption of green supply chain management in developing countries: role of consumer cooperation, eco-design, and green marketing - Shafiul Bashar; Daoping Wang; Marwah Rafiq (Environmental Science and Pollution Research, 2023)

How carbon emission prices accelerate net zero: Evidence from China's coal-fired power plants - Qingyang Wu; Chang Tan; Daoping Wang; Yongtao Wu; Jing Meng; Heran Zheng (Energy Policy, 2023)

Transportation carbon emission reduction potential and mitigation strategy in China - Caiquan Bai; Zhijun Chen; Daoping Wang (Science of The Total Environment, 2023)

Pricing-decision analysis of green supply chain with two competitive manufacturers considering horizontal and vertical fairness concerns - Daoping Wang; Genhasi Ge; Yu Zhou; Mengying Zhu (Environmental Science and Pollution Research, 2022)

An efficient micropropagation protocol, chemical components, and hypoglycemic activity for Cremastra appendiculata (D. Don) Makino pseudobulbs - Ningxian Yang; Daoping Wang; Yanyan Gao; Enming Hu; Xiaosong Yu; Sijing Peng; Jun Ji; Ming-sheng Zhang (In Vitro Cellular & Developmental Biology - Plant, 2022)

Economic impacts of climate-induced crop yield changes: evidence from agri-food industries in six countries - Daoping Wang; Katie Jenkins; Nicole Forstenhäusler; Tianyang Lei; Jeff Price; Rachel Warren; Rhosanna Jenkins; Dabo Guan (Climatic Change, 2021)

Assessing changes and driving factors of energy consumption in China over 2000–2014: a perspective of final demand - Liwen Liu; Daoping Wang; Caiquan Bai (Environmental Science and Pollution Research, 2021)

Characterization of milk protein composition of the Yangtze finless porpoise - Xianyuan Zeng; Minmin Chen; Zhigang Liu; Daoping Yu; Shiang‐Lin Huang; Jiwei Yang; Fei Fan; Ding Wang; Yujiang Hao; Ghulam Nabi (Marine Mammal Science, 2019)

Effects of fish community on occurrences of Yangtze finless porpoise in confluence of the Yangtze and Wanhe Rivers - Xiaoke Zhang; Daoping Yu; Huili Wang; An Wan; Minmin Chen; Feng Tao; Zunrong Song (Environmental Science and Pollution Research, 2015)